2018
DOI: 10.1016/j.addbeh.2018.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Situational fears: Association with negative affect-related smoking cognition among treatment seeking smokers

Abstract: Despite the consistent clinically-significant relation between smoking and anxiety and its disorders, there is limited understanding of how specific fears relate to smoking processes. To isolate therapeutic targets for smoking-anxiety treatment development, there is a need to identify the underlying situational fears most related to smoking processes. Thus, the present study examined the association between interoceptive, agoraphobic, and social fears in terms of clinically significant negative affect-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
(72 reference statements)
2
1
0
Order By: Relevance
“…To date, only one study has reported on mean scores regarding specific fears associated with preoperative anxiety [5]. The range of mean VAS scores (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) is consistent with mean mNRS scores of the present study (2.4-3.9). However, results concerning items that were used in both surveys seem to be inconsistent.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…To date, only one study has reported on mean scores regarding specific fears associated with preoperative anxiety [5]. The range of mean VAS scores (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) is consistent with mean mNRS scores of the present study (2.4-3.9). However, results concerning items that were used in both surveys seem to be inconsistent.…”
Section: Discussionsupporting
confidence: 88%
“…Results concerning the latter variable are consistent with numerous publications suggesting a relationship between cigarette smoking, anxiety and anxiety disorders (e.g. [32,33]). However, the magnitude of the reported association is surprising and raises doubts whether the reported effects can be attributed to "smoking" solely.…”
Section: Predictors Of Preoperative Anxietysupporting
confidence: 91%
“…Similarly, negative reinforcement, especially the alleviation of withdrawal‐related negative emotions, is also a key motivation for smoking (Hall et al., 2015 ). There is evidence that quitters with social anxiety are more likely to start smoking again (Bakhshaie et al., 2018 ). Researchers also found that a fear of obesity tends to disrupt the process of quitting smoking in the smoking population (Bush et al., 2014 ).…”
Section: Introductionmentioning
confidence: 99%